Diseño y construcción de una máquina mezcladora de balanceado con capacidad de 100 kg/h para implementación en la empresa Avícola Avitecnic del Ecuador. - Gómez Chachapoya, Darío Javier (2023)
The present technological proposal was developed with the purpose of reducing time and increasing production in the mixing and homogenization processes of the Poultry company AVITECNIC of Ecuador, through the implementation of a horizontal mixing machine with a capacity of 100 kg/h, improving the homogeneity quality of the balancing. To meet the objectives of the proposal, a horizontal mixing machine was designed and built that consists of a mixing system of two helical slats arranged in opposite directions. This system is ideal for flours, granulated powders and liquids, meeting the requirements and needs. of the company. The material selected for the container and the mixing system was A304 stainless steel due to its corrosion resistance properties which make it suitable for contact with food, while ASTM A36 structural steel was used for the structure. The power required in the shaft connected to the helical slats is transmitted by a 2hp single-phase electric motor at 1750 rpm connected to a two-stage speed reduction system, the first system is given by a 3-inch driving pulley and a driven pulley. 17 inches with two bands, the second reduction system consists of a 17-tooth sprocket connected to the driven pulley and a 102-tooth Catarina, obtaining a constant speed of 45 rpm at the output to guarantee quality homogenization for the product.